Ambivalent Islam: the identity construction of Muslims under Portuguese colonial rule - Machaqueiro, Mário (2012)
This article wishes to contribute to the study of the historical processes that have been spotting Muslim populations as favourite targets for political analysis and governance. Focusing on the Portuguese archives, civil as well as military, the article tries to uncover the most conspicuous identity representations (mainly negative or ambivalent) that members of Portuguese colonial apparatus built around Muslim communities living in African colonies, particularly in Guinea-Bissau and Mozambique. The paper shows how these culturally and politically constructed images were related to the more general strategies by which Portuguese imagined their own national identity, both as ‘European’ and as ‘coloniser’ or ‘imperial people’. The basic assumption of this article is that policies enforced in a context of inter-ethnic and religious competition are better understood when linked to the identity strategies inherent to them. These are conceived as strategic constructions aimed at the preservation, the protection and the imaginary expansion of the subject, who looks for groups to be included in and out-groups to reject, exclude, aggress or eliminate. We think that most of the inter-ethnic relationships and conflicts, as well as the very experience of ethnicity, are born from this identity matrix.